Pay it forward: refuse dump from leaf-cutting ants promotes caterpillar digestive performance by increasing plant nitrogen content - Lescano, María Natalia (2019)
1. The activity of soil-disturbing animals that increase soil nutrients can affect the carbon : nitrogen (C : N) ratio of plants, which, in turn, may determine the transfer of energy and nutrients through higher trophic levels. However, the strength and sign of this indirect effect depend on whether enhanced nutrient substrates increase plant foliar nutrients and/or plant defensive traits. 2. We investigated how the nutrient-rich refuse dumps of the leaf-cutting ant Acromyrmex lobicornis, as a result of their direct effects on thistles, indirectly impact the growth rate and digestive performance of a generalist chewing herbivore. We also included the application of commercial fertilisers to test whether the enhanced soil nutrients comprises the mechanism behind the impact of refuse dumps on the upward cascade effects. 3. Thistles growing on nutrient-rich substrates (i.e. ant refuse dumps and fertilised soil) had more and larger leaves, up to 80% lower C : N ratios, and higher physical defences compared to plants growing on steppe soil. Caterpillars showed an enhanced digestive performance and growth rate when feed on nutrient-rich plants and were able to adjust the C : N ratio of their excretion to regulate the relative acquisition of nutrients. 4. The positive effect of nutrient-rich substrates on caterpillar feeding efficiency suggest that the enhanced nutritional quality of the thistles could compensate for the negative effects of the increased physical defences. The results of the present study indicate how organisms that increase soil nutrient availability may diminish the stoichiometric constraints at the base of food chains, enhancing the development and growth rate of herbivores and, thus, indirectly mediating plant–herbivore interactions.